Incidence and natural history of hen's egg allergy in the first 2 years of life—the EuroPrevall birth cohort study. Issue 3 (22nd December 2015) - Xepapadaki, P.; Fiocchi, A.; Grabenhenrich, L.; Roberts, G.; Grimshaw, K. E. C.; Fiandor, A.; Larco, J. I.; Sigurdardottir, S.; Clausen, M.; Papadopoulos, N. G.; Dahdah, L.; Mackie, A.; et al.
Abstract: Background: Parents and health staff perceive hen's egg allergy (HEA) as a common food allergy in early childhood, but the true incidence is unclear because population‐based studies with gold‐standard diagnostic criteria are lacking. Objective: To establish the incidence and course of challenge‐confirmed HEA in children, from birth until the age of 24 months, in different European regions. Methods: In the EuroPrevall birth cohort study, children with a suspected HEA and their age‐matched controls were evaluated in 9 countries, using a standardized protocol including measurement of HE‐specific immunoglobulin E‐antibodies in serum, skin prick tests, and double‐blind, placebo‐controlled food challenges (DBPCFC). Results: Across Europe, 12 049 newborns were enrolled, and 9336 (77.5%) were followed up to 2 years of age. In 298 children, HEA was suspected and DBPCFC was offered. HEA by age two was confirmed in 86 of 172 challenged children (mean raw incidence 0.84%, 95% confidence interval (95% CI) 0.67–1.03). Adjusted mean incidence of HEA was 1.23% (95% CI 0.98–1.51) considering possible cases among eligible children who were not challenged. Centre‐specific incidence ranged from United Kingdom (2.18%, 95% CI 1.27–3.47) to Greece (0.07%). Half of the HE‐allergic children became tolerant to HE within 1 year after the initial diagnosis. Conclusions: The largest multinational European birth cohort study on food allergy with gold‐standard diagnostic methods showed that the mean adjusted incidence of HEA was considerably lower than previously documented, although differences in incidence rates among countries were noted. Half of the children with documented HEA gained tolerance within 1 year postdiagnosis.